Maximizing brand image building as a semi-pub café through emotional branding - Izzah, Nurul; Sumartias, Suwandi; Perbawasari, Susie (Manajemen Komunikasi, 2024)
This research discusses a café in Makassar City called Pyur for You Café, which decided to rebrand when it was threatened with permanent closure due to the Covid-19 pandemic in 2021. The café previously had a work-friendly concept and was then rebranded as a semi-pub café, which implemented emotional branding. This study aims to analyze the Pyur For You café, discuss the background of the Pyur For You café in choosing to apply emotional branding to a new café concept, discuss the process of creating its identity, and analyze how the Pyur For You café applies the emotional aspect of branding to a new concept. So that consumers are attached to the café and prefer the Pyur For You Café over other competitors. This research is a qualitative case study with informants from the café, namely, the owner and staff, who understand the application of emotional branding. The author also randomly selected five consumers who met in the Pyur For You café area to conduct in-depth interviews. The results of the interviews regarding rebranding were analyzed through the four basic pillars of emotional branding, according to Marc Gobe. The findings show that the Pyur For You café has implemented the basic concept of emotional branding, which is communicated through relationships with consumers, the interior design of the café, events held, and food served. However, its application can still be maximized.